Spatiotemporal patterns of PFAS in water and crop tissue at a beneficial wastewater reuse site in central Pennsylvania. Issue 6 (3rd November 2022) - Mroczko, Olivia; Preisendanz, Heather E.; Wilson, Christopher; Mashtare, Michael L.; Elliott, Herschel A.; Veith, Tamie L.; Soder, Kathy J.; Watson, John E.
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are a collective name for thousands of synthetic compounds produced to enhance consumer and industrial products since the 1940s. They do not easily degrade, and some are known to pose serious ecological and human health concerns at trace concentrations (ng L −1 levels). Per‐ and polyfluoroalkyl substances persist in treated wastewater and are inadvertently introduced into the environment when treated wastewater is reused as an irrigation source. The Pennsylvania State University (PSU) has been spray‐irrigating its wastewater at a 2.45 km 2 mixed‐use agricultural and forested site known as the "Living Filter" since the 1960s. To understand the spatiotemporal patterns of 20 PFAS at the Living Filter, water samples were collected bimonthly from fall 2019 through winter 2021 from the PSU's wastewater effluent and from each of the site's 13 monitoring wells. Crop tissue was collected at the time of harvest to assess PFAS presence in corn silage and tall fescue grown at the study site. Total measured PFAS concentrations in the monitoring wells ranged from nondectable to 155 ng L −1, with concentrations increasing with the direction of groundwater flow. Concentrations within each well exhibited little temporal variability across sampling events, with mixed relationships between PFAS and groundwater elevation observed between wells. Further, >84% of the PFAS present in livestock feed crops were short‐chain compounds, with PFAS consumed annually by livestock fed crops harvested from the site estimated to be 2.46–7.67 mg animal −1 yr −1 . This research provides insight into the potential impacts of long‐term beneficial reuse of treated wastewater on groundwater and crop tissue quality. Core ideas: Twenty PFAS were tracked in wastewater, groundwater, and crops at a beneficial reuse site. Groundwater concentrations ranged from nondetectable to 155 ng L −1 and increased with groundwater flow direction. PFOS and PFOA were as high as 22 and 30 ng L −1, respectively, in all samples from 13 groundwater wells. PFAS in corn silage and fescue tissue were 0.97 and 11.3 μg kg −1 dw, respectively. More than 84% of PFAS in cattle feed crops were short‐chain compounds (PFBA, PFPeA, PFHxA).